PHYSICAL EDUCATION AND SPORT PLAY AN IMPORTANT SOCIAL ROLE IN THE EDUCATIONAL SYSTEM - Azizov Mirzohid Mirzolim o`g`li,; Sulaymanov Dostonbek Ravshanbekovich, (Journal of new century innovations, 2024)
Annotation: This article is about physical education and sport play an important social role in the educational system. This article discusses the features of maintaining human health through physical education. The important role of physical culture in human life is noted. The main types of exercise to maintain health are listed, such as running, pulling up, swimming, and stretching exercises.